The Problematic Representation of Women: An Analysis of Ratna Indraswari Ibrahim's Literary Text - Moh. Fathoni (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Representation of women in literature develops parallelly with the productivity of literary texts. This representation is inevitably intertwined with a discourse that cannot be separated from power relations. Thus, the position and identity of women are vulnerable to domination and subordination. However, women are constructed as subjects and objects, allowing negotiation and contestation to emerge. This article examines the problematic representation of women in Ratna Indraswari Ibrahim's text,